Difference in functional assessment of individual stenosis severity in serial coronary lesions between resting and hyperemic pressure-wire pullback: Insights from the GIFT registry. (1st August 2020) - Warisawa, Takayuki; Howard, James P.; Kawase, Yoshiaki; Tanigaki, Toru; Omori, Hiroyuki; Cook, Christopher M.; Ahmad, Yousif; Francis, Darrel P.; Akashi, Yoshihiro J.; Matsuo, Hitoshi; Davies, Justin E.
Abstract: Background: Identifying the individual hemodynamic significance of tandem coronary artery lesions can be complicated by the crosstalk phenomenon which occurs between serial stenoses under hyperemic conditions. Physiological assessments performed under resting conditions are considered to be, theoretically, less affected by the hemodynamic interaction between serial coronary stenoses. The purpose of this study was to assess whether pressure-wire (PW) pullback measurements at rest and during hyperemia provided different information as to which stenosis appeared to be most functionally significant. Methods: In consecutive patients with angiographically discrete serial lesions, physiological lesion predominance (i.e. proximal or distal) was defined according to the pressure gradient along the vessels on PW-pullback trace. We used instantaneous wave-free ratio (iFR) based assessment as the reference standard and compared fractional flow reserve (FFR) based and hyperemic-iFR based lesion predominance. Results: Eighty-eight vessels (70 patients, mean age 70.3 ± 9.4 years, 80% male) were included in this study. Median iFR, FFR and hyperemic-iFR were 0.85 (interquartile range [IQR]: 0.74 to 0.91), 0.73 (IQR: 0.65 to 0.80) and 0.60 (IQR: 0.49 to 0.71), respectively. When judged against iFR-pullback based physiological assessment, lesion predominance changed in 22.7% (20/88) in FFR and in 20.5% (18/88) in hyperemic-iFR, respectively. There was no statistical difference between FFR and hyperemic-iFR for the impact on these changes ( p  = 0.77). Conclusions: In serial coronary lesions, hyperemic PW-pullback disagreed with resting PW-pullback on the lesion-specific identification of ischemia in approximately 20% of cases, either in whole cardiac cycle or in wave-free period. Highlights: In serial stenoses within a coronary artery, there is a hemodynamic interaction between lesions known as crosstalk. We directly compared resting and hyperemic pressure-wire pullbacks in serial lesions. For identification of the most physiologically severe stenosis, the resting and hyperemic indices disagree in 20% of vessels. This level of discordance was similar for hyperemic indices during both the whole cardiac cycle and the wave free period.